Characterisation of purified acetylcholinesterase (EC 3.1.1.7) from Oreochromis mossambica brain tissues - Tham, Lik Gin; Perumal, Natarajan; Ahmad, Siti Aqlima; Sabullah, Mohd Khalizan (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
This study reports on the characterization of a purified AChE from Oreochromis mossambica brain extract. The purification protocol involved the application of custom-synthesized affinity chromatography gel (Edrophonium–Sephacryl S-400) and the use of high performance liquid chromatography system (HPLC). Soluble AChE was partially purified 27.9 fold with a highest specific activity around 73.1 × 103 U/mg proteins. The partially purified AChE higher capability to hydrolyse acetylthiocholine (ATC) and shows less degradation against propionylthiocholine (PTC) and also butyrylthiocholine (BTC). Based on enzyme kinetic analysis, the partially purified AChE exhibits the apparent Michaelis constants Km, for ATC, PTC and BTC in the range of 125, 260 and 600 µM and the maximum velocities Vmax were 276, 59 and 36 µmol/min/mg protein, respectively. The apparent inhibition constant (ki) values of eserine, propidium and carbofuran were 0.24 µM-1min-1, 65 µM-1min-1 and 0.41 µM-1min-1 µM-1min-1, respectively. The purified enzyme is apparently an AChE since it capable to hydrolyzes ATC at a higher rate compared to other synthetic substrates, at pH 7.0 and 25ºC, and is inhibited by it specific inhibitor which is eserine but not by iso-OMPA.